Factor affecting Medical errors Reporting among medical team in Pediatric Hospitals in Gaza governorate - AbuMustafa, Dr. Ayman M.; Jaber, Mayada (Jour Med Resh and Health Sci, 2019)
Background: Collecting data on medical errors is essential for improving patient safety, but a lot of factors affecting error reporting by physicians and nurses. These factors may be individual or institutional in the health care system and sometimes mandatory. The barriers preventing doctors and nurses in pediatric hospitals from reporting medicals errors are poorly understood. the objective of the study was to identify the factors affecting medical error reporting by medical team among pediatric hospitals in Gaza Governorate, Gaza Strip. Methods: The study design was a cross-sectional study using a questionnaire. A total of 86 doctors and nurses were selected by the purposive sample in pediatric hospitals in Gaza Governorate (Al Nasr, Al Durra & Al Rantisi hospitals). Data analysis performed using Statistical Package for the Social Sciences software version 23, and a p-value less than 0.05 was statistically significant. Results: The factors affecting medical error reporting by physicians and nurses were organizational barriers (59.2%), barriers due to fear (72.4%), cultural barriers (73.1%), respectively. The First causes preventing medical error reporting by physicians and nurses were staff worry (76.9%) followed by fear of lawsuits (legal and financial penalties) (75.3%), the fear of questioning competence (74.2%), work pressures (68.6%) and finally insufficient staff number (67.9%). Conclusion and recommendations: elevated work pressures and insufficient staff number with staff worry from lawsuits lead to medical error not reporting among pediatric hospitals in Gaza Governorate. Change the culture and knowledge about medical error reporting will support doctors and nurses to reporting the medical error and avoid repeated again by focusing on safety rather than productivity during clinical work essential for improving patient safety